An Overview of Father Involvement in Parenting Children with Dyslexia - Lestari Hidayati, Iwa Dwi; Novita, Shally; Noer, Afra Hafny (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Father involvement in child care is very important for child development. Based on several studies, father involvement can affect child development. The purpose of this study is to provide an overview of how the involvement of working fathers in providing care for children who have dyslexia. The method used is qualitative with a phenomenological approach. The research participants were three fathers. Data obtained through interviews with openended questions via zoom. The result showed that the three participants still took their time to be involved in parenting, then on the other hand, it was also found that the difficulties experiences by fathers in caring for dyslexic children were due to limited interaction communication skills and behavioral issues of dyslexic children.